2011
DOI: 10.1093/infdis/jir714
|View full text |Cite
|
Sign up to set email alerts
|

Presence of CXCR4-Using HIV-1 in Patients With Recently Diagnosed Infection: Correlates and Evidence for Transmission

Abstract: The results confirmed the relation between CXCR4-use at diagnosis and low baseline CD4+ T cell counts. Significantly more CXCR4-use was predicted in 01_AE infections, which may impose constraints on the use of CCR5 antagonists in certain regions of the world. Observations from the transmission cluster analysis contradict the hypothesis that R5 viruses are selected at transmission, and support the idea that R5 or X4/DM infections result from a stochastic process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
64
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 48 publications
17
64
0
3
Order By: Relevance
“…Several previously reported studies used deep sequencing to predict HIV-1 coreceptor usage by sequencing of the HIV-1 env V3 region (26,(45)(46)(47)(48). Most of those studies used 454 sequencing, which was limited by homopolymer errors and relative low throughput compared to the Illumina or IonTorrent platform (25).…”
Section: Discussionmentioning
confidence: 99%
“…Several previously reported studies used deep sequencing to predict HIV-1 coreceptor usage by sequencing of the HIV-1 env V3 region (26,(45)(46)(47)(48). Most of those studies used 454 sequencing, which was limited by homopolymer errors and relative low throughput compared to the Illumina or IonTorrent platform (25).…”
Section: Discussionmentioning
confidence: 99%
“…Early in the course of infection, most HIV isolates utilize CCR5 (56,74,86); however, several recent reports have demonstrated that CXCR4-utilizing viral subpopulations are found in as many as 10 to 50% of recently infected individuals (1,14). In addition, CXCR4-utilizing viruses emerge in many patients later in the course of infection (55,66).…”
Section: Cd45romentioning
confidence: 99%
“…This has made it possible to seek genotypic and phenotypic differences between T/F Env proteins and those derived from chronically infected individuals (chronic control [CC] Envs). Several phenotypic characteristics are clearly associated with transmission: T/F Envs virtually always use CCR5 rather than CXCR4 or other noncanonical coreceptors (2,(16)(17)(18) and generally infect T cells but not macrophages (2,13,15,19) as a result of requiring relatively high levels of CD4 to mediate virus entry (20)(21)(22)(23)(24)(25). Other phenotypic and genotypic traits that have been linked to transmission are less well defined: Envs isolated from acute infection have sometimes been reported to be more neutralization sensitive (19), have on average fewer putative N-linked glycosylation sites (1,26), and have shorter variable loops (1,(27)(28)(29) compared to Envs isolated from chronically infected individuals.…”
mentioning
confidence: 99%